Transmitted Defiance: Genocide Resistance across Generations of Armenian Women - Nikki Marczak (International Journal of Armenian Genocide Studies, 2019)
During and after the genocide, Armenian women resisted: silently, discreetly, but sometimes also loudly and overtly; and often in spiritual or cultural ways. A common thread through women’s testimonies is a spirit of defiance – a sense of dignity, resilience and a refusal to allow their identity to be destroyed – that they have passed on to future generations. This article presents the concept of transmitted defiance, a gendered process that occurs transgenerationally. A hundred years after the genocide, women who are descended from survivors often view their relatives’ actions as inspiration for their own lives. Further, many have inherited rebelliousness and an indelible sense of Armenian identity from their mothers, grandmothers and great-grandmothers, which manifests in their own contemporary acts of resistance.